PEG-coated vesicles from Pluronic/lipid mixtures for the carrying of photoactive erythrosine derivatives - de Freitas, Camila Fabiano (2019)
Liposomes are very attractive membrane models and excellent drug delivery systems. Concerning their drug delivery aspects, the mixing liposomes with biocompatible copolymers allows for stability and the incorporation of several drugs. We developed PEG coated vesicles from the mixture of DPPC and F127 Pluronic copolymer to obtain long-circulating nanoparticles (mixed vesicles). We employed an innovative process previously developed by us: a small amount of F127 mixed in DPPC, thin film preparation, followed by hydration (lipids plus F127) using a bath sonicator cleaner type, forming unilamellar spherical vesicles with diameter ∼100 nm. The formed PEG coated vesicles were incorporated with the xanthene dye Erythrosine B (ERY), and its ester derivatives as photosensitizers (PS) for photodynamic proposes. The F127/DPPC mixed vesicles promoted a higher PS incorporation, and with better thermal and kinetic stability, at least 60 days, when compared to conventional DPPC liposome. The binding constant and quenching analysis revealed that with a higher PS hydrophobicity, PS affinity increases toward the nanoparticle and results in a deeper PS location inside the lipid bilayer. An increment in the fluorescence quantum yield was observed, while the PS singlet oxygen generations remained high. Dialysis studies demonstrated that PS were released based on their hydrophobicity. Permeation analysis showed that all PS can reach the deeper regions of the skin. The Decyl Ester derivative/nanoparticle exhibited high photoactivity against Caco-2 cancer cells (in vitro studies). The PEG coated from F127/DPPC mixed vesicles are very promising nanocarriers for erythrosine and its derivatives.